(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this paper we shall define and discuss about some special characters of Pell’s equation and a very simple verified results on Pell’s equation to show that, one can find more solution of Pell’s equation which give rise to next some another solution by continued fraction in a very simple manner. With the help of convergence of continued fraction expansion of in the Pell’s equation , we shall find out Diophantine pair solution of Pell’s equation under certain condition. At last we shall get some recent results on Pell’s equation.